Exploring the use of vlog-portfolio to develop oral fluency and active listening through peer- scaffolding - Shuib, Muhammad Asyraf (2020)
With the upsurge of technological advancement, the internet and social media, many studies on instructional practices in ESL classrooms with the use of technology have been carried out to match the 21st century learning climate. Practitioners, curriculum designers and scholars continue to explore the potentials of using various media tools that can support teaching and learning. Today, frequent engagement with social media and the internet has allowed learners to sharpen their English language communication skills. Vygotsky’s Zone of Proximal Development Theory which emphasizes the use of scaffolding for language learning, and Siemen’s Theory of Connectivism which gives emphasis on network and learning underpin the current study. This study explored the potentials of using video blogging portfolio to improve speaking fluency among ESL learners at a higher learning institution in Malaysia. The current study employed an exploratory single case study approach to mitigate the existing gap that is linked to the limited opportunity and exposure Malaysian ESL learners have to communicate using the L2. In the effort of encouraging communication using the L2 beyond the confinement of a classroom, the researchers employed the use of the social media platform, Instagram as an eportfolio – redefined as the vlog-portfolio to systematically compile learners’ communicative activities. A learner centered approach was applied where participants of the study engaged in a weekly video-blogging assignment about varying themes and topics for 10 weeks. An instructional module was designed and incorporated into an existing curriculum as a project-based learning assessment. This video blog project was conducted in pairs. Episodic interviews were carried out to identify the scaffolding techniques employed by the learners in completing each task. Fluency and pause rates were also measured. The findings revealed that learners showed developmental patterns in their speech fluency rates. A focused group interview showed that learners were able to practice English extensively with the vlog-portfolio project. Besides producing speech, they were also encouraged to partake in assessing their spoken language performance through peer-reviewing sessions using a qualitative case study document which encouraged self-assessment, peer-assessment and reflective practices among learners. It can be concluded that the vlog-portfolio is beneficial as a learning tool as it adds novelty to instructional practices, encourages scaffolding, active listening, helps learners improve on fluency, and encourages learners to practice speaking using a social media platform.